Analisis Profitabilitas Untuk Mengukur Kinerja Keuangan Manajemen Hotel (Studi Kasus pada UNY-Hotel Yogyakarta). - Ismani Ismani; Ngadirin Setiawan; Andian Ari Istiningrum (Jurnal Pendidikan Akuntansi Indonesia, 2011)
The purpose of this research is to measure financial performance of UNY-Hotelmanagement by using profitability ratios, such as Net Profit Margin (NPM) and Return ofTotal Assets (ROA). The research is an evaluative research that is done by analyzingfinancial statement of UNY-Hotel and interviewing management in order to get more deeplyinformation. The result of this research shows that financial performance of UNY-Hotel islow due to NPM at 26.89 % that is lower than the target at 40% and ROA at 6.41% that islower than the interest rate (10% – 12% per annum). This result indicates that there isinefficiency in managing assets and expenses.Kata Kunci: kinerja keuangan, profitabilitas, net profit margin, return on asset, tingkatperputaran aset